2021
DOI: 10.52312/jdrs.2021.78446
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the COVID-19 pandemic on orthopedic surgeries in a tertiary referral center

Abstract: Objectives: The aim of this study is to investigate the effect of the novel coronavirus-2019 (COVID-19) pandemic on the operational trends in the orthopedic surgery department of a tertiary referral center. Patients and methods: A total of 305 orthopedic surgical procedures in 245 patients (136 males, 109 females; mean age: 34±26.6 years; range, 0 to 91 years) between March 16th and June 27th, 2020 were retrospectively analyzed. The same period of the year before including 860 procedures i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…On the other hand, the increase in the number of orthopedic emergency surgeries that was reported in our study may be due to an increase in the number of reported falls from heights, stairs, ladders, etc. [26,27]. In addition, the reduction in the number of emergency hernia repair surgeries reported is in line with previous studies [28].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the increase in the number of orthopedic emergency surgeries that was reported in our study may be due to an increase in the number of reported falls from heights, stairs, ladders, etc. [26,27]. In addition, the reduction in the number of emergency hernia repair surgeries reported is in line with previous studies [28].…”
Section: Discussionsupporting
confidence: 90%
“…12 Several studies demonstrated that sport-related injuries decreased considerably during the pandemic. 7,18,19 As the Government limits any outdoor activities, this policy implies pediatric trauma admission as well. 17 Additionally, patients' fears of contracting COVID-19 may plague them, leading them to seek telemedicine consultations over ER visits to limit in-person contact.…”
Section: Discussionmentioning
confidence: 99%
“…Only emergency or urgent surgeries were performed to avoid a negative impact on patient outcomes. 7 Additionally, orthopedic professional societies developed guidelines and protocols for determining which surgeries should be prioritized and which should be delayed. 8,9 Regarding the emergency time due to the outbreak, many surgeons transferred to various units, including emergency rooms, specialized COVID-19 units, and critical care units.…”
Section: Introductionmentioning
confidence: 99%
“…A worrisome decline in the volume of orthopaedic and trauma specialists has been well-documented over the past few decades [ 16 , 17 , 18 , 19 ]. Compounding the existing workforce shortages, the disturbances to global healthcare systems due to the COVID-19 pandemic caused further negative disruptions to orthopaedic and trauma care and education [ 20 , 21 , 22 , 23 ]. These realities have further re-echoed the established potential of leveraging computer-based technologies to enhance the efficiency of orthopaedic training and practice.…”
Section: Introductionmentioning
confidence: 99%